Development of power control module in RFID reader circuit: a mentor graphic simulation approach - Uddin, Md. Jasim; Ibrahimy, Muhammad Ibn; Reaz, Mamun Bin Ibne (2008)
As the technology of automatic identification using radio frequency called RFID which is expected to be the alternative of the next generation barcode improves, concerns to the privacy infringement grow harder. In recent years, there has been growing interest in the development of communication systems for the localization and the identification of objects. This paper concerns the development of power splitter design for power control module in RFID reader circuit. In this work, a noble transformer type Wilkinson unequal power splitter was developed using Mentor Graphic. In order to extract the best RF performance from the power splitter, it was optimally designed using a newly proposed method. The power splitter supported highly improved RF characteristics in industrial scientific and medical (ISM) band gigahertz regions. It exhibited a bandwidth that extended from 2.5 GHz to 3 GHz, return loss 19.6 dB and isolation values 5.4 dB.